2006
DOI: 10.1097/01.ta.0000215583.08765.ce
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Polymorphonuclear Neutrophil Surface Receptor Expression and Migratory Activity After Isolation: Comparison of Whole Blood and Isolated PMN Preparations from Normal and Postfracture Trauma Patients

Abstract: PMN isolation results in priming for migration, which has a relatively greater impact upon PMN in trauma patients. The observation that PMN activity may decline but priming potential remains enhanced is novel. Further refinements of whole blood and isolated PMN techniques are clearly warranted. This may help to resolve the mismatch in clinical and scientific experience in those patients with major fractures requiring surgical stabilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…During the first days after trauma, circulating PMNs prove to be primed, resulting in not only an increased migratory capacity but also in enhanced cytotoxic functions [33,[40][41][42]. The levels of neutrophil elastase as indicator of systemic activation of PMNs rise shortly after injury [15].…”
Section: Cellular Responsementioning
confidence: 98%
“…During the first days after trauma, circulating PMNs prove to be primed, resulting in not only an increased migratory capacity but also in enhanced cytotoxic functions [33,[40][41][42]. The levels of neutrophil elastase as indicator of systemic activation of PMNs rise shortly after injury [15].…”
Section: Cellular Responsementioning
confidence: 98%
“…In contrast, Thorén et al (26) recently reported that NK cells accelerate spontaneous apoptosis of isolated PMNs. In this study, to avoid the PMN isolation procedures that have been reported to alter PMN responses (21,42,43), we analyzed PMN apoptosis by flow cytometry in whole-blood conditions. In these conditions, with whole-blood PMN activation by GG, a polysaccharide extracted from A. fumigatus, we demonstrated that NK cells are a critical trigger of PMN apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 The relationship between priming that has occurred, residual priming potential, and functional activity are areas which currently remain ill-defined. 23 Thus, these primed PMN are capable of causing increased tissue damage by degranulation and respiratory burst activity once they have homed to the lung and site of injury in large numbers and are activated by local factors. Targeting PMN degranulation and preventing the sequestration of large numbers of primed/activated PMN in the lung and other tissues may provide potential therapeutic avenues in preventing the development of ARDS/MOF.…”
Section: Discussionmentioning
confidence: 99%